Self-Ascribed Paranormal Ability: Reflexive Thematic Analysis - Drinkwater, Kenneth Graham; Dagnall, Neil; Walsh, Stephen; Sproson, Lisa; Peverell, Matthew; Denovan, Andrew (Frontiers in Psychology, 2022)
This study investigated personal perceptions (involvements) and comprehensions (interpretations) of self-ascribed paranormal abilities. Twelve participants with supposed supernatural powers took part in semi-structured interviews exploring the origin, phenomenology, and nature of their powers. Interview transcripts were analysed using reflexive thematic analysis (RTA), a qualitative method that identifies patterns within data. Four major themes expressed meanings and representations held by participants: Formative Influences (sub-themes: Gifted Family Members and Anomalous Occurrence), (Inter) Subjective Paranormal Experience (sub-themes: Transcendental/Mystic and Extra-Sensory Perception), Embodied Processes (sub-theme: Control), and Perception of Reality (two sub-themes: Self-Awareness and Fantastic/Surreal Perceptions). Consideration of themes identified an inextricable link between perception, interpretation, and belief in ability. Within narratives, interviewees outlined, contextualised, and established the validity of their powers. They drew upon supporting autobiographical evidence from their life histories and obfuscated and/or discounted conventional explanations. Generally, accounts reflected individual attempts to comprehend and justify the nature and experience of professed abilities. The authors discuss these processes and suggest ways to extend and develop ensuing research.